Cost-Effective Optical Fiber Curvature Sensor With Ultrahigh Sensitivity Based on Two Microcollapses in Silica Capillary - Ruikai Xue; Yu Mao; Yuxi Zhang; Yi Liu; Kunjian Cao; Shiliang Qu (IEEE Photonics Journal, 2018)
We proposed an optical fiber curvature sensor based on two microcollapses in silica capillary that was spliced between single-mode fibers. Only commercial fiber fusion splicer was needed in the fabrication process. The two microcollapses in the silica capillary can improve the interference effect of light modes with ring distribution surrounding the ultrafine air core (internal diameter of 5 μm), and the axisymmetric mode distribution is easy to be affected by the curving of the capillary. The proposed fiber structure can be used as a cost-effective curvature sensor owing to its simple fabrication process, low fabrication cost, good repeatability, ultrahigh sensitivity (885.62 nm/m−1), and low temperature crosstalk (29 pm/°C).